Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles